(untitled) (Jurnal Destinasi Pariwisata, 2025)
Bakas Village is a pioneering tourism village established through Klungkung Regent Decree No. 2 of 2017, boasting natural, cultural, and man-made tourism potential. However, since its designation as a tourism village, tourism development in Bakas Village has been suboptimal. This is due to the limited human resources available to manage the existing tourism potential. The COVID-19 pandemic in 2020 also led to a decline in tourism visits and revenues, contributing to the low level of local community participation. The purpose of this study is to analyze the tourism potential of Bakas Village and assess the level of community participation in its development. The research method used is qualitative, utilizing both qualitative and quantitative data types. Data collection techniques include observation, interviews, and documentation. The informant selection technique used purposive sampling, with descriptive qualitative data analysis. The results of the study indicate that the form of community participation in Bakas Village is actually carried out through labor, property, and skills, while not tangible through thoughts, ideas or concepts. The level of community participation in the development process of Bakas Tourism Village, at the planning and benefit-taking stages is still considered less than optimal because only a portion of the community is represented, at the implementation stage there is already some but less than optimal, and at the evaluation stage there is still no. Increasing community participation still requires encouragement from influential parties so that the empowerment and development of tourism villages can run more effectively and sustainably.